Spatial Distribution of Erosion on Corn Fields in Boalemo Regency, Gorontalo Province - Achmad Nur Fahry Machmud; Fitryane Lihawa; M. Fahry Djuraini; M. Luthfi A.S Ibrahim (Journal of Applied Geoscience and Engineering, 2026)
The spatial distribution of surface erosion on corn fields in Boalemo Regency, Gorontalo Province is a significant concern. Boalemo Regency is known for its corn production, but the land clearing for corn cultivation, especially on steep slopes, has led to land degradation, triggering floods and landslides. This study aims to examine the spatial distribution of surface erosion on corn agricultural land in Boalemo Regency, covering all corn plantations in an area of 181,672.83 hectares. The RUSLE (Revised USLE) method was used to analyze soil erosion. The analysis of surface erosion levels was conducted based on the stages of corn planting, including the land preparation and planting stages. The results indicated that the total erosion during the land preparation stage was 2474870411 tons per year, while during the corn planting stage, it was 1150961410 tons per year. The level of erosion was found to be very severe, covering an area of 46706.92 hectares (25.71%) during the land preparation stage and 33852.80 hectares (18.63%) during the planting stage.